MICROPILE TECHNIQUES FOR SOIL TREATMENT AND FOUNDATION ENHANCEMENT IN EXISTING STRUCTURES (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
Micropiles are an effective means of improving the ground. It is also used for the support of foundations. Micropiles are widely used in geotechnical engineering. It is used for strengthening weak soils. Moreover, it is also used for the rehabilitation of existing structures. The paper shows a specialized study for Micropiles systems as an engineering process used for soil treatment within Princesses Residential Complex 2 in Najaf Governorate. The engineering of these structures is such that all of them are residential buildings each two-story built of brick with mat foundation of thickness 30 cm. Observed cracking in walls & foundation along with severe subsidence in soil. The method involves site investigation which Includes the drilling of 3 wells of 15m depth. Soils were found to be sandy (SP) and had very high SO3 (10.491), TSS (25.591), OM(0.135), GYPSUM (22.453), The soil is weak up to 6 meters depth (SPT = 15 blows), and after 6 meters depth it increases to more than 50 blows, Where the groundwater level is 13 meters deep, The failure is due to the breaks of drainage pipes and constant irrigation of the gardens which dissolve salts, organic materials and gypsum, leaving voids behind which cause massive subsidence of the soil. Results show improvement in load-bearing capacity, reduction in settlement, and stability. The study demonstrates the effectiveness of Micropiles in complex soil conditions and limited construction spaces.
Keywords: Micropiles; Soil Treatment; Ground Improvement; mat Foundation Engineering; Settlement Control.